(untitled) (Materiali di Estetica. Terza serie, 2017)
The paper analyses Kafka’s fragment as one of the first trace of the author’s creative journey. I will read Man darf nicht sagen in the complexity of Kafka’s literary work, investigating the recurrence of stylistic features such as negation, irony, uses of subjunctive and indicative verbal moods, as well as the semantic nuances of the German modal verb dürfen. Nevertheless, I won’t reduce such stylistic peculiarities to a mere linguistic exercise. I argue that Franz Kafka inscribes in Man darf nicht sagen the seeds, the signals of a never ending subjective confrontation with the question of transmission, memory, subjectivity, and testimony in name of an Otherness: in a word, with the question of the Law. Keywords: Franz Kafka; Psychoanalysis; the Work of the Negative